A Note on Someone (Else): An Island Repair Solution and Its Competitors - Saab, Andrés Leandro (2015)
It is shown that sluicing sentences involving the unexpected absence of "else" modification for the wh-remnant (Barros 2012) are best analyzed as instances of island repair under ellipsis, specifically, as repair of the Coordinate Structure Constraint. Two alternative analyses are discussed, namely, Barros´ solution in terms of a predicative strategy and a potential mutual entailment approach à la Merchant 2001, and it is shown that they have to face serious empirical challenges.